Composite silicon negative electrode material as well as preparation method and application thereof
By growing metal organic frame materials in situ on the surface of the nanosilicon anode material of all-solid state batteries, forming nitrogen-doped porous carbon materials, and generating sulfide solid electrolytes in situ, the problem of volume expansion of the negative electrode materials during charging and discharging is solved, and the energy density and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202411894218.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
AI Technical Summary
The volume expansion of the negative electrode material of an all-solid state battery during charging and discharging, causing the electrode material to rupture and powder, shortening the battery life, and the specific capacity of the negative electrode material in the prior art is low, affecting the energy density of the battery.
The metal organic frame material is generated on the surface of the nanosilicon material by in-situ growth method, and nitrogen-doped porous carbon material is formed by calcining treatment, and finally sulfide solid electrolyte is generated on the surface of the Si-NC material to form the Si-NC-SE composite silicon negative electrode material.
The conductivity and cyclic stability of the composite silicon negative electrode material are improved, the energy density and cyclic performance of the battery are enhanced, the expansion and rupture of the electrode are reduced, and the safety of the battery is improved.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode materials, and in particular to a composite silicon negative electrode material, a preparation method thereof, and an application thereof. Background Art
[0002] With the continuous development of new energy technologies, all-solid-state batteries have shown broad application prospects in electric vehicles, energy storage systems and other fields due to their advantages such as high energy density, long cycle life and safety performance. However, the commercial application of all-solid-state batteries still faces many challenges, such as low conductivity of active materials in electrodes and poor interface contact between electrode materials and solid electrolytes. Among them, the negative electrode material of all-solid-state batteries has a great influence on the performance of the battery. The negative electrode material must remain chemically stable within the operating voltage range of the battery, not react adversely with the solid electrolyte, and have a high specific capacity, that is, the material per unit mass can store more charge. At the same time, the negative electrode material needs to have good electronic conductivity to quickly transmit electrons. Although the negative electrode material itself does not need to have high ionic conductivity like the electrolyte, it should allow lithium ions (or other active ions) to be smoothly embedded and de-embedded in its structure. As a high-energy-density negative electrode material, the application of Si materials in all-solid-state batteries is also limited by the above requirements.
[0003] For example, the patent with the publication number of CN 117096301A relates to a ternary composite nano silicon-carbon-based negative electrode material and its preparation method, and a solid-state battery. The technical solution of the patent uses metal organic framework materials and nano silicon as precursors, and obtains a ternary composite nano silicon-carbon-based negative electrode material by calcining the precursor and washing and centrifuging it multiple times. However, the ternary composite nano silicon-carbon material prepared by this method contains nickel elements, and the negative electrode material containing nickel elements will expand in volume during the charging and discharging process, especially when nickel reacts with lithium to form lithium nickel oxide. This volume change will cause the electrode material to break and pulverize, thereby shortening the life of the battery. At the same time, the nickel element may undergo phase change at high temperatures, which may affect the thermal stability of the battery and increase the risk of thermal runaway and safety accidents. Relatively speaking, the overall specific capacity of the negative electrode material prepared by this method is low, which may affect the energy density of the entire battery cell, and this method only improves the electronic conductivity of Si, and the ionic conductivity of the material is low. Summary of the invention
[0004] The purpose of the present application is to provide a composite silicon negative electrode material suitable for sulfide-based all-solid-state batteries, a preparation method and application thereof, by coating nitrogen-doped porous carbon material (NC) on the surface of Si material through in-situ generation technology, and in-situ generating sulfide solid electrolyte, thereby improving the conductivity of the composite silicon negative electrode material and the cycle stability of the sulfide-based all-solid-state battery using the composite silicon negative electrode material.
[0005] In a first aspect, the present application provides a method for preparing a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery, characterized in that it comprises the following steps: (1) Generate metal organic framework materials by in situ growth method on the surface of nano-silicon materials; (2) Carbonizing the metal organic framework material on the surface of the nano-silicon material to form a nitrogen-doped porous carbon material through calcination to obtain a Si-NC material; (3) A sulfide solid electrolyte is generated on the surface of the Si-NC material by an in-situ growth method to obtain a Si-NC-SE composite silicon negative electrode material.
[0006] The present invention adopts an in-situ growth method to directly form a metal organic framework material on a nano silicon material. Compared with mixed nano silicon materials and formed metal organic framework materials, the binding force between the in-situ grown MOFs and the nano silicon material is usually stronger than that of the physical mixing method, which helps to maintain the structural stability of the material during the charge and discharge process of the battery and reduce the problems of material shedding and volume expansion. Through the in-situ growth method, a uniform layer of MOFs can be formed on the surface of the nano silicon material, which can better wrap the nano silicon material and avoid the problems of agglomeration and uneven distribution that may occur during the physical mixing process. This helps to achieve better interface contact between the electrode material and the electrolyte, forming a continuous conductive network, thereby improving the transmission efficiency of electrons and ions and reducing the resistance of the electrode. At the same time, the in-situ grown MOFs can provide more active sites, increase the specific surface area of the electrode material, and reduce the interface impedance between the electrode material and the electrolyte, thereby improving the capacity and cycle performance of the battery.
[0007] Furthermore, the metal organic framework material is carbonized by calcination to obtain a nitrogen-doped porous carbon material, wherein the porous structure has a high specific surface area, can provide more active sites, increase the capacity of the electrode material, and is conducive to the penetration of electrolytes and the diffusion of lithium ions, while maintaining a good electronic transmission network, having good electrical conductivity, and can serve as a bridge for electronic transmission, thereby improving the conductivity of the entire electrode material. Since the porous carbon material has a large number of pores, the structure of the porous carbon material is relatively loose and has a certain compressibility. These pores can provide additional space when the silicon material expands in volume, so that the silicon material will not be subject to excessive restrictions when expanding, thereby reducing and dispersing internal stress to adapt to volume changes, rather than being easily broken like dense materials, and can buffer the volume changes caused by lithium insertion and extraction during the charging and discharging process of the silicon material, reducing the expansion and rupture of the electrode. At the same time, nitrogen doping can increase the electrochemical activity of the electrode material, and the nitrogen atoms in the nitrogen-doped porous carbon material can serve as a host for lithium ions, increase the transmission rate of lithium ions, and improve the cycle stability and rate performance of the battery.
[0008] Furthermore, by generating a sulfide solid electrolyte on the surface of the Si-NC material through the in-situ growth method, a good interface contact can be formed between the Si-NC material and the sulfide solid electrolyte, thereby reducing the interface resistance and improving the overall performance of the battery. At the same time, the in-situ grown sulfide solid electrolyte can better adapt to the volume change of the Si-NC material during the charging and discharging process, and reduce the stress caused by volume expansion and contraction.
[0009] In summary, due to the high theoretical capacity of silicon materials, the stability of nitrogen-doped porous carbon materials, and the high ionic conductivity of sulfide solid electrolytes, the composite silicon negative electrode material can provide higher energy density.
[0010] In some embodiments, the step (1) specifically includes: pre-treating the nano-silicon material and mixing it with a metal salt solution and an organic ligand solution, and generating a layer of metal organic framework material on the surface of the nano-silicon material by an in-situ growth method, wherein the metal salt is a zinc salt and / or a cobalt salt, and the organic ligand is an organic compound containing nitrogen atoms.
[0011] In some embodiments, the organic ligand is 2-methylimidazole.
[0012] In an embodiment, the nanosilicon material is directly mixed with a metal salt solution and an organic ligand solution so that the surface of the nanosilicon material is in direct contact with the metal ions, making it easier for it to form initial adsorption with the metal ions, and the metal ions on the surface of the nanosilicon material can serve as nucleation sites, which helps the subsequent uniform growth of metal-organic framework materials on the surface of the nanosilicon material.
[0013] In some embodiments, in step (1), the particle size of the nano-silicon material is 50-100 nm.
[0014] During the charging cycle, silicon will experience a large volume effect. The larger the silicon particle size, the greater the amount of lithium embedded, and the more obvious the volume effect. Therefore, it is possible to damage the electrolyte coating on the surface. Therefore, the particle size of the nano-silicon material is controlled to 50~100nm, the volume effect is small, and the coating stability is higher.
[0015] In some embodiments, in step (1), the stirring temperature is 20-30°C, the stirring speed is 300-350 rpm, the stirring time is 10-12 h, the calcination temperature is 500-800°C, the calcination time is 1-4 h, and the heating rate is 1°C / min-5°C / min.
[0016] In the embodiment, the nano-silicon material is uniformly dispersed by stirring, and fully reacts with the metal ions and organic ligands to form a uniform metal organic framework material on the surface of the nano-silicon material. At the same time, the carbonization degree of the metal organic framework material is controlled by controlling the calcination temperature, calcination time, and heating rate to maintain the integrity of the pore structure.
[0017] In some embodiments, the step (3) specifically includes placing the Si-NC material in a mixed solution containing a lithium source, a sulfur source, a phosphorus source and a dispersant, generating a sulfide solid electrolyte in situ on the surface of the Si-NC material, and obtaining a Si-NC-SE composite silicon negative electrode material after drying and sintering.
[0018] In some embodiments, in step (3), the mixed solution containing a lithium source, a sulfur source, and a phosphorus source contains at least two of lithium sulfide, lithium oxide, lithium hydroxide, lithium chloride, silicon sulfide, cobalt sulfide, phosphorus pentasulfide, phosphorus trisulfide, tetraphosphorus nonasulfide, tetraphosphorus trisulfide, tetraphosphorus hexasulfide, and tetraphosphorus pentasulfide, and the solvent of the mixed solution is n-heptane or p-xylene.
[0019] In the embodiment, using n-heptane or p-xylene as a solvent can help the precursor powders such as sulfide to be evenly dispersed in the solution, reduce the interaction force between the powders, and reduce the agglomeration phenomenon, so as to form a uniform sulfide solid electrolyte in the subsequent heat treatment process, and the uniformly dispersed sulfide solid electrolyte helps to improve the ionic conductivity of the electrolyte, thereby improving the overall electrochemical performance. At the same time, the volatility of n-heptane and p-xylene helps to quickly remove the solvent during the drying process, thereby improving the efficiency and uniformity of the heat treatment.
[0020] In some embodiments, in step (3), the solid content of the mixed solution is 30% to 60%.
[0021] In some embodiments, in step (3), the drying temperature is 80-100°C, the drying time is 12-24 hours, the sintering temperature is 200-500°C, the sintering time is 3-6 hours, and the heating rate is 1°C / min-5°C / min.
[0022] In the embodiment, the solid content is controlled to ensure that there are enough solid components in the solution to form a dense sulfide electrolyte layer, and the evaporation of the solvent and the formation of the sulfide electrolyte are ensured by controlling the appropriate temperature and time.
[0023] In a second aspect, a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery is provided, characterized in that the composite silicon negative electrode material is prepared by the preparation method described in any one of the first aspects.
[0024] In a third aspect, an application of the composite silicon negative electrode material according to any one of the first aspect and the second aspect is provided, characterized in that the composite silicon negative electrode material is used in an all-solid-state battery.
[0025] The composite silicon negative electrode material suitable for sulfide-based all-solid-state batteries provided by the present invention, its preparation method and application have beneficial effects including but not limited to the following: (1) The preparation method of the composite silicon negative electrode material provided by the present invention adopts an in-situ growth method to directly form a metal organic framework material on the nano silicon material. Compared with the mixed nano silicon material and the formed metal organic framework material, it helps to maintain the structural stability of the material during the charge and discharge process of the battery, reduces the problem of material shedding and volume expansion, and helps to achieve better interface contact between the electrode material and the electrolyte, forming a continuous conductive network, thereby improving the transmission efficiency of electrons and ions and reducing the resistance of the electrode. At the same time, the in-situ grown MOFs can provide more active sites, increase the specific surface area of the electrode material, and reduce the interface impedance between the electrode material and the electrolyte, thereby improving the capacity and cycle performance of the battery.
[0026] (2) The preparation method of the composite silicon negative electrode material provided by the present invention is to obtain a nitrogen-doped porous carbon material by carbonizing the metal organic framework material through calcination treatment, wherein the porous structure has a high specific surface area, can provide more active sites, increase the capacity of the electrode material, and is conducive to the penetration of the electrolyte and the diffusion of lithium ions. At the same time, it maintains a good electron transmission network and has good electrical conductivity. It can serve as a bridge for electron transmission and improve the conductivity of the entire electrode material. Since the porous carbon material has a large number of pores, the structure of the porous carbon material is relatively loose and has a certain compressibility. These pores can provide additional space when the silicon material expands in volume, so that the silicon material will not be too restricted when expanding, thereby reducing and dispersing the internal stress to adapt to the volume change, instead of being easily broken like dense materials. It can buffer the volume change of the silicon material caused by lithium insertion and extraction during the charging and discharging process, and reduce the expansion and rupture of the electrode. At the same time, nitrogen doping can increase the electrochemical activity of the electrode material. The nitrogen atoms in the nitrogen-doped porous carbon material can serve as a host for lithium ions, increase the transmission rate of lithium ions, and improve the cycle stability and rate performance of the battery.
[0027] (3) The preparation method of the composite silicon negative electrode material provided by the present invention generates a sulfide solid electrolyte on the surface of the Si-NC material through an in-situ growth method, which can form a good interface contact between the Si-NC material and the sulfide solid electrolyte, reduce the interface resistance, and improve the overall performance of the battery. At the same time, the in-situ grown sulfide solid electrolyte can better adapt to the volume change of the Si-NC material during the charging and discharging process, and reduce the stress caused by volume expansion and contraction. DETAILED DESCRIPTION
[0028] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0029] The present application provides a method for preparing a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery, characterized in that it comprises the following steps: (1) Generate metal organic framework materials by in situ growth method on the surface of nano-silicon materials; (2) Carbonizing the metal organic framework material on the surface of the nano-silicon material to form a nitrogen-doped porous carbon material through calcination to obtain a Si-NC material; (3) A sulfide solid electrolyte is generated on the surface of the Si-NC material by an in-situ growth method to obtain a Si-NC-SE composite silicon negative electrode material.
[0030] The present invention adopts an in-situ growth method to directly form a metal organic framework material on a nano silicon material. Compared with mixed nano silicon materials and formed metal organic framework materials, the binding force between the in-situ grown MOFs and the nano silicon material is usually stronger than that of the physical mixing method, which helps to maintain the structural stability of the material during the charge and discharge process of the battery and reduce the problems of material shedding and volume expansion. Through the in-situ growth method, a uniform layer of MOFs can be formed on the surface of the nano silicon material, which can better wrap the nano silicon material and avoid the problems of agglomeration and uneven distribution that may occur during the physical mixing process. This helps to achieve better interface contact between the electrode material and the electrolyte, forming a continuous conductive network, thereby improving the transmission efficiency of electrons and ions and reducing the resistance of the electrode. At the same time, the in-situ grown MOFs can provide more active sites, increase the specific surface area of the electrode material, and reduce the interface impedance between the electrode material and the electrolyte, thereby improving the capacity and cycle performance of the battery.
[0031] The following will describe in detail a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery, a preparation method thereof, and an application thereof provided in the present application in combination with specific embodiments.
[0032] The present application provides a method for preparing a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery, characterized in that it comprises the following steps: (1) Generate metal organic framework materials by in situ growth method on the surface of nano-silicon materials; (2) Carbonizing the metal organic framework material on the surface of the nano-silicon material to form a nitrogen-doped porous carbon material through calcination to obtain a Si-NC material; (3) A sulfide solid electrolyte is generated on the surface of the Si-NC material by an in-situ growth method to obtain a Si-NC-SE composite silicon negative electrode material.
[0033] In some embodiments, the step (1) specifically includes: pre-treating the nano-silicon material and mixing it with a metal salt solution and an organic ligand solution, and generating a layer of metal organic framework material on the surface of the nano-silicon material by an in-situ growth method, wherein the metal salt is a zinc salt and / or a cobalt salt, and the organic ligand is an organic compound containing nitrogen atoms.
[0034] In some embodiments, the pretreatment of the nano-silicon material specifically includes: placing the nano-silicon material in a vacuum drying oven for drying, the drying temperature is 80-100° C., and the drying time is 20-24 hours.
[0035] In some embodiments, the organic ligand is 2-methylimidazole.
[0036] In some embodiments, in step (1), the particle size of the nano-silicon material is 50-100 nm.
[0037] In some embodiments, in step (1), the stirring temperature is 20-30°C, the stirring speed is 300-350 rpm, the stirring time is 10-12 h, the calcination temperature is 500-800°C, for example, 500°C, 600°C, 700°C or 800°C, the calcination time is 1-4 h, for example, 1 h, 2 h, 3 h or 4 h, and the heating rate is 1°C / min-5°C / min.
[0038] In some embodiments, the step (3) specifically includes placing the Si-NC material in a mixed solution containing a lithium source, a sulfur source, a phosphorus source and a dispersant, generating a sulfide solid electrolyte in situ on the surface of the Si-NC material, and obtaining a Si-NC-SE composite silicon negative electrode material after drying and sintering.
[0039] In some embodiments, the sulfide solid electrolyte includes Li6PS5Cl, Li7P3S 11 Or one of Li6PS4.
[0040] In some embodiments, in step (3), the mixed solution containing a lithium source, a sulfur source, and a phosphorus source contains at least two of lithium sulfide, lithium oxide, lithium hydroxide, lithium chloride, silicon sulfide, cobalt sulfide, phosphorus pentasulfide, phosphorus trisulfide, tetraphosphorus nonasulfide, tetraphosphorus trisulfide, tetraphosphorus hexasulfide, and tetraphosphorus pentasulfide, and the solvent of the mixed solution is n-heptane or p-xylene.
[0041] In some embodiments, in step (3), the solid content of the mixed solution is 30% to 60%, for example, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0042] In some embodiments, in step (3), the drying temperature is 80-100°C, for example, 30°C, 90°C or 100°C, the drying time is 12-24h, for example, 12h, 16h, 20h or 24h, the sintering temperature is 200-500°C, for example, 200°C, 300°C, 400°C or 500°C, the sintering time is 3-6h, for example, 3h, 4h, 5h or 6h, and the heating rate is 1°C / min-5°C / min. Example 1
[0043] This embodiment provides an all-solid-state battery equipped with a Si-NC-Li6PS5Cl composite silicon negative electrode material, and the preparation steps are as follows: S1. Pretreatment of nano-Si materials: Si powder with a particle size of 100 nanometers was placed in a vacuum drying oven for drying at a temperature of 80°C for 24 hours; S2, in situ growth of MOF: 0.87g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) was dissolved in 30mL of methanol to prepare a cobalt ion solution, and 0.98g of 2-methylimidazole was dissolved in 10mL of methanol to prepare a ligand solution. Then the Si powder (3g) treated in S1 was mixed with the two solutions and stirred at 25°C at a speed of 300rpm for 12h. Then, the Si-ZIF-67 composite material was obtained by centrifugation, washing, drying and other steps. The centrifugal speed was 1500rpm, and the centrifugal time was 1min each time. The washing solvent was methanol. The drying temperature was 80°C and the drying time was 12h.
[0044] S3, high temperature carbonization of MOF material to form nitrogen-doped porous carbon material (NC): the Si-ZIF-67 material obtained in S2 was carbonized at 800°C for 4 h under nitrogen flow conditions with a heating rate of 1°C / min to obtain Si-NC; S4, in-situ generation of sulfide solid electrolyte: Si-NC obtained in S3 is mixed with Li2S, P2S5, LiCl and n-heptane in a zirconia tank to obtain a mixed solution, wherein the solid content of the mixed solution is 36%; then the mixture is run at a speed of 500 rpm for 8 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven for drying, wherein the drying temperature is 100°C and the drying time is 24 hours; a dry mixed conductive additive precursor is obtained. All the above operations are carried out in an inert atmosphere. The mixed precursor is placed in a muffle furnace for high-temperature sintering to obtain a Si-NP-Li6PS5Cl composite silicon negative electrode material. During the sintering process, the sintering temperature is 500°C, the sintering time is 6 hours, and the heating rate is 1°C / min.
[0045] S5. Preparation of all-solid-state battery: The Si-NP-Li6PS5Cl composite material obtained in S4 is used as the negative electrode to assemble a solid-state battery. The assembly steps are as follows: Preparation of positive electrode: positive electrode, according to the percentage of amount, lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) content is 70%, the content of solid electrolyte (Li6PS5Cl) is 27%, and the content of conductive agent (VGCF) is 3%; in a glove box filled with argon, lithium nickel cobalt manganese oxide, sulfide solid electrolyte, and conductive agent are ground in a mortar for 10 minutes until they are evenly mixed to obtain a composite positive electrode; Solid electrolyte: The solid electrolyte is Li6PS5Cl; Assembly of all-solid-state battery: first weigh 0.1gLi6PS5Cl solid electrolyte powder and place it in the mold sleeve, cold press it at 360MPa for 5min to obtain the sulfide solid electrolyte layer, then lay the positive electrode and Si-NC-Li6PS5Cl negative electrode on both sides of the sulfide solid electrolyte layer, and then cold press it at 50MPa pressure, and finally tighten the screws to seal the mold to obtain an all-solid-state battery. Example 2
[0046] Example 2 was conducted with reference to Example 1, except that the cobalt nitrate hexahydrate (Co(NO3)2·6H2O) salt in S2 in Example 1 was replaced with zinc nitrate hexahydrate (Zn(NO3)2·6H2O), and S3 was carbonized at 700°C for 3 hours to obtain the ZIF-8 carbonized Si-NC material. The remaining steps were the same as in Example 1. Example 3
[0047] Example 3 refers to Example 1 for experiments. Compared with Example 1, the only difference is that the process parameters for in-situ generation of sulfide solid electrolyte in S4 are different. Specifically, Si-NC is mixed with Li2S, P2S5, LiCl and n-heptane in a zirconia tank to obtain a mixed solution, wherein the solid content of the mixed solution is 60%; then the mixture is run at a speed of 500 rpm for 8 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven for drying, the drying temperature is 80°C, the drying time is 12 hours, and a dry mixed conductive additive precursor is obtained. All of the above operations are carried out in an inert atmosphere. The mixed precursor is placed in a muffle furnace for high-temperature sintering to obtain Si@NP@Li6PS5Cl. During the sintering process, the sintering temperature is 500°C, the sintering time is 3 hours, and the heating rate is 5°C / min. Example 4
[0048] Example 4 was experimented with reference to Example 1. Compared with Example 1, the only difference is that the solvent used in the in-situ generated sulfide solid electrolyte in S4 is different. The solvent used in Example 4 is p-xylene. Example 5
[0049] Example 5 refers to Example 1 for experiment. Compared with Example 1, the only difference is that the sulfide solid electrolyte generated in situ in S4 is different. Specifically, Si-NC is mixed with Li2S, P2S5 and n-heptane in a zirconia tank to obtain a mixed solution, wherein the solid content of the mixed solution is 36%; then the mixture is run at a speed of 500 rpm for 8 hours to obtain a wet mixture, and then the wet mixture is placed in a vacuum drying oven and dried at 100°C for 24 hours, wherein the drying temperature is 100°C and the drying time is 24 hours; a dry mixed conductive additive precursor is obtained. The solid content of the mixture is 36%. All the above operations are carried out in an inert atmosphere. The mixed precursor is placed in a muffle furnace for high-temperature sintering, sintered at 260°C for 3 hours, and the heating rate is 1°C / min to obtain Si-NP-Li7P3S 11 In the sintering process, the sintering temperature is 260° C., the sintering time is 3 h, and the heating rate is 1° C. / min. Example 6
[0050] The only difference between Example 6 and Example 1 is that the high-temperature carbonization treatment conditions in S3 are different. Specifically, the Si-ZIF-67 material is carbonized under a nitrogen flow condition of 500°C for 1 h with a heating rate of 5°C / min to obtain Si-NC. Comparative Example 1
[0051] In this comparative example, the nano-silicon material is directly used as the negative electrode, that is, NC and sulfide solid electrolyte are not generated in situ.
[0052] The all-solid-state batteries obtained from the above embodiments and comparative examples were subjected to the first coulombic efficiency, 0.1C discharge specific capacity, 0.3C discharge specific capacity, and 0.3C cycle 100 cycle capacity retention rate performance tests. During the test, the charge cut-off voltage was 4.2V and the discharge cut-off voltage was 2.2V. The results are shown in Table 1.
[0053] Table 1 Performance test table sample First coulombic efficiency (%) 0.1C discharge specific capacity (mAh / g) 0.3C discharge specific capacity (mAh / g) 100 cycles capacity retention rate (%) Example 1 86.43 199.20 173.50 89 Example 2 81.56 187.60 165.20 84 Example 3 79.32 182.43 152.70 75 Example 4 85.65 197.80 170.20 86 Example 5 83.25 191.47 165.20 84 Example 6 80.53 185.70 158.40 77 Comparative Example 1 75.46 174.30 143.20 64 By comparing Example 1 and Example 2 with Comparative Example 1, it can be seen that the first coulombic efficiency, 0.1C discharge specific capacity, 0.3C discharge specific capacity, and 0.3C cycle 100 capacity retention rate of Example 1 and Example 2 are significantly higher than those of Comparative Example 1, indicating that the in-situ carbonization of the MOF material and the in-situ generation of the sulfide solid electrolyte improve the electronic conductivity and ionic conductivity of Si itself.
[0054] By comparing Example 1 with Example 3 and Example 6, it can be seen that the first coulombic efficiency, 0.1C discharge specific capacity, 0.3C discharge specific capacity, and 0.3C cycle 100 capacity retention rate of Example 1 are higher. Therefore, the conditions required for in-situ generation of sulfide solid electrolyte and high-temperature carbonization in Example 1 are optimal.
[0055] By comparing Example 1 with Example 4, it can be seen that when the sulfide solid electrolyte is generated in situ, the dispersion effect of p-xylene is better than that of n-heptane, but p-xylene is more toxic, more expensive, and has poorer battery performance.
[0056] By comparing Example 1 with Example 5, it can be seen that when the sulfide solid electrolyte adopts Li6PS5Cl, the performance of the prepared Si-NC-Li6PS5Cl composite silicon negative electrode material is better. In summary, after reading the contents of this application, those skilled in the art can understand that the aforementioned application contents can be presented only by way of example and may not be restrictive. Although not explicitly stated here, those skilled in the art can understand that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are within the spirit and scope of the exemplary embodiments of this application.
Claims
1. A method for preparing a composite silicon negative electrode material suitable for a sulfide-based all-solid-state battery, characterized in that: The following steps are involved: (1) Generate metal organic framework materials by in situ growth method on the surface of nano-silicon materials; (2) Carbonizing the metal organic framework material on the surface of the nano-silicon material to form a nitrogen-doped porous carbon material through calcination to obtain a Si-NC material; (3) A sulfide solid electrolyte is generated on the surface of the Si-NC material by an in-situ growth method to obtain a Si-NC-SE composite silicon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The step (1) specifically comprises: pre-treating the nano-silicon material, mixing it with a metal salt solution and an organic ligand solution, and generating a layer of metal organic framework material on the surface of the nano-silicon material by an in-situ growth method, wherein the metal salt is a zinc salt and / or a cobalt salt, and the organic ligand is an organic compound containing nitrogen atoms.
3. The preparation method according to claim 1, characterized in that: In the step (1), the particle size of the nano-silicon material is 50-100 nm.
4. The preparation method according to claim 1, characterized in that: In the step (1), the stirring temperature is 20-30°C, the stirring speed is 300-350 rpm, the stirring time is 10-12 h, the calcination temperature is 500-800°C, the calcination time is 1-4 h, and the heating rate is 1°C / min-5°C / min.
5. The preparation method according to claim 1, characterized in that: The step (3) specifically includes placing the Si-NC material in a mixed solution containing a lithium source, a sulfur source, a phosphorus source and a dispersant, generating a sulfide solid electrolyte in situ on the surface of the Si-NC material, and obtaining a Si-NC-SE composite silicon negative electrode material after drying and sintering.
6. The preparation method according to claim 1, characterized in that: In the step (3), the mixed solution containing the lithium source, the sulfur source and the phosphorus source contains at least two of lithium sulfide, lithium oxide, lithium hydroxide, lithium chloride, silicon sulfide, cobalt sulfide, phosphorus pentasulfide, phosphorus trisulfide, tetraphosphorus nonasulfide, tetraphosphorus trisulfide, tetraphosphorus hexasulfide and tetraphosphorus pentasulfide, and the solvent of the mixed solution is n-heptane or p-xylene.
7. The preparation method according to claim 1, characterized in that: In the step (3), the solid content of the mixed solution is 30% to 60%.
8. The preparation method according to claim 1, characterized in that: In the step (3), the drying temperature is 80-100°C, the drying time is 12-24 hours, the sintering temperature is 200-500°C, the sintering time is 3-6 hours, and the heating rate is 1°C / min-5°C / min.
9. A composite silicon negative electrode material suitable for sulfide-based all-solid-state batteries, characterized in that: The composite silicon negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. The use of the composite silicon negative electrode material according to any one of claims 1 to 9, characterized in that: The composite silicon negative electrode material is used in an all-solid-state battery.
Citation Information
Patent Citations
Ternary composite nanometer silicon-carbon-based negative electrode material, preparation method thereof and solid-state battery
CN117096301A
Cited By
Porous silicon carbon negative electrode material, negative electrode plate, all-solid-state battery and preparation method of all-solid-state battery
CN121282127A